2012
DOI: 10.2174/187152812803251033
|View full text |Cite
|
Sign up to set email alerts
|

A Proprietary Topical Preparation Containing EGCG-Stearate and Glycerin with Inhibitory Effects on Herpes Simplex Virus: Case Study

Abstract: The effects of a proprietary topical formulation containing EGCG-stearate in 100% glycerin USP were studied in two volunteer patients with recurrent herpes simplex (HSV) type 1. Application during early onset (prodromal stage) in a patient with herpes labialis prevented lesion progression. In a second patient with herpetic stomatitis, application of the formula during a later stage (inflammation stage) led to a remarkably shortened duration of symptoms. In contrast, a third patient provided 100% glycerin USP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Palmitoyl-EGCG therefore offers a potentially useful approach to prevent infection by topical application on epithelial tissues. A case study has been reported recently that the topical application of lipophilic EGCG could be a potential effective treatment for HSV (Zhao et al 2012). Use of p-EGCG could have significant public health benefits, and warrants further study in appropriate models.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoyl-EGCG therefore offers a potentially useful approach to prevent infection by topical application on epithelial tissues. A case study has been reported recently that the topical application of lipophilic EGCG could be a potential effective treatment for HSV (Zhao et al 2012). Use of p-EGCG could have significant public health benefits, and warrants further study in appropriate models.…”
Section: Discussionmentioning
confidence: 99%
“…These healing properties are attributable to its abundant polyphenolic catechins, such as the epigallocatechin-3-gallate, EGCG, which accounts for up to 50 mg in a single cup of tea [10]. During the last two decades, extensive evidence has emerged to support a wide spectrum of anti-bacterial [11-14], anti-viral [15-17], or anti- …”
Section: Introductionmentioning
confidence: 99%
“…We reported previously that 50 µM EGCG-p completely blocks the infectivity of herpes simplex-1 virus (HSV-1) in Vero cells; this compound showed significantly higher efficacy than watersoluble EGCG [19]. The antiviral effect of lipophilic EGCG was further validated in a clinical trial treating herpes labialis caused by herpes simplex virus; it demonstrated high efficacy, without reported side effect [11,12]. Newly published data from hand sanitizer formulation testing demonstrated that, using 50% Tissue Culture Infective Dose (TCID50) assay methods, a novel alcoholbased sanitizer formulation containing EGCG-p resulted in a mean 6-log 10 -reduction of human poliovirus 1 (PV-1) infectivity (i.e., one million-fold reduction), exceeding by 100-fold the mandatory in vitro >4 log 10 -reduction of PV-1 infectivity for virucidal agents set by the US (EPA), EU, Canada and China [22].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have indicated that epigallocatechin-3-gallate (EGCG) and its lipid-soluble derivatives, especially EGCG-palmitate (EGCG-p), could be strong candidates for the next generation of antiviral and virucidal materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. EGCG is a major polyphenol component of extracts from dry leaves of the Camellia sinensis (tea) plant, and its antiviral activities have been studied widely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation